Amelanotic acral melanoma misdiagnosed as verruca plantaris - Wei Deng; Ruixing Yu; Yong Cui; Zhancai Zheng (Sociedade Brasileira de Dermatologia, 2019)
Abstract: We report a case of amelanotic acral melanoma in a 42-year-old Chinese woman. Ten months previously the patient found a 2-cm asymmetric erythematous macular plaque on her left sole. The lesion was diagnosed as verruca plantaris by every physician the patient consulted. One month ago, an enlarged lymph node was detected in the left groin, which biopsy reported as metastatic melanoma. Dermoscopy suggested verruca plantaris, and positron emission tomography (PET) revealed increased glucose metabolism in the macular plaque. Finally, biopsy of the plaque revealed amelanotic melanoma. Misdiagnosis and diagnostic delay are usually associated with poorer patient outcomes. Awareness of atypical presentations of acral melanoma is thus important for decreasing misdiagnosis rates and improving patient outcomes.